Thought and Political Judgment - Roger W. H. Savage (Études Ricoeuriennes / Ricoeur Studies, 2021)
Hannah Arendt’s claim that thinking is the last defense against the moral outrages of criminal political regimes sets the problematic of good and evil in relief. Human freedom, Paul Ricœur reminds us, is responsible for evil. The avowal of the evil of violence is thus the condition of our consciousness of the freedom to act anew. Aesthetic experience’s lateral transposition onto the planes of ethics and politics highlights our capacity to respond to exigencies in apposite ways.  Exemplary representations of the good, the right, and the justexpress a desire for being. Eros is accordingly the law of every work, word, deed, or act that answers to a difficulty, challenge, or crisis. Bound to living experiences, thought attains its true height through interrogating, demystifying, and vacating frozen norms, standards, and mores. Judgment actualizes thought’s liberating effects in answer to the demands of the situations in which we find ourselves.